The therapeutic and pharmacological potential of cannabidiol (Research, Society and Development, 2020)
The article reviews the therapeutic and pharmacological effects of cannabidiol, characterizing possible adverse and toxicological effects. This is an integrative bibliographic review carried out in the databases of PubMed, Science Direct and LILACS with the descriptors “drug effects”, “canabidiol” and “treatment” in english, using the Boolean operator AND and restricted to the years 2015 to July 2020. 89 articles were initially found, from the application of the inclusion criteria, it was possible to select the 27 articles constituting the work, from which information about authors, objective, sample, type of research, dosage and result for the composition of results table were obtained. It can be concluded that cannabidiol has therapeutic effects in pathologies related to the central nervous system and the immune system, places where it has mechanisms of action and that intoxication events are not frequently reported, however it has a vast report of adverse effects, in mostly light such as drowsiness and gastric discomfort.